Pengaruh Diskon Harga dan Testimoni Pelanggan terhadap Keputusan Pembelian di Shopee (Studi pada Mahasiswa Manajemen UNIMED) - Zebua, Ovan Krisadelman; Zahra, Atika; Anggiani, Eka; Siahaan, Kevin Valensius; Faradilla, Ageng Jihan; Siregar, Zulkarnain (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study examines the influence of price discounts and customer testimonials on purchasing decisions among Management students at Universitas Negeri Medan who use the Shopee platform. The research addresses the growing reliance of students on digital marketplaces and the limited empirical evidence on how economic and social stimuli jointly shape online buying behavior in this demographic. Using a quantitative associative approach, data were collected from 60 respondents through a structured Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The findings reveal that price discounts do not have a significant partial effect on purchasing decisions (Sig. = 0.254 > 0.05), indicating that promotional price reductions alone may be insufficient to drive students’ buying actions. In contrast, customer testimonials show a strong and significant partial effect (Sig. = 0.000 < 0.05), highlighting the importance of reliable reviews in reducing uncertainty and reinforcing trust in online transactions. Simultaneously, both variables significantly influence purchasing decisions (F = 82.222; Sig. = 0.000 < 0.05), with an R² value of 0.743, meaning that 74.3% of the variation in purchasing decisions is explained by the model. These findings underline the dominant role of testimonial-based credibility in student consumer behavior and suggest that Shopee’s marketing strategies may benefit more from strengthening authentic user reviews than from relying solely on price promotion mechanisms.